EXPERIMENT AND SIMULATION RESEARCH OF THE OPTIMUM INTERFERENCE OF HI-LOCK ASSEMBLY - XIE JieDong; CHEN Guo; ZENG XinLiang; SHU MaoSheng; LUO Yun; GAO Hong; ZHENG QiHui (Jixie qiangdu, 2018)
At present, the high lock bolt assembly standard of our country are come from abroad, lack of relevant theoretical and experimental research. Fatigue gain mechanism of high lock bolt interference on the base of different layer thickness is researched,through the method of combining the fatigue test and finite element simulation in a certain type of aircraft aluminum alloy structure. First, the fatigue test was designed and tested, and the results were analyzed by S-N curve, detail fatigue rating（DFR） and fracture location. Then, the finite element modeling and simulation are used to explain the experimental phenomena, and the mechanism of the interference fit to the fatigue gain is studied. Finally, the comprehensive detail fatigue rating results and the finite element simulation results are obtained, which are the standard recommended values of the high lock bolt assembly,and verified existing installation specifications, ensure the assembly quality of a certain type of aircraft.